2021
DOI: 10.1002/dad2.12188
|View full text |Cite
|
Sign up to set email alerts
|

A survey of smartphone and interactive video technology use by participants in Alzheimer's disease research: Implications for remote cognitive assessment

Abstract: Introduction:Participants from a longitudinal cohort study were surveyed to evaluate the practical feasibility of remote cognitive assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Smartphones, which are becoming ubiquitous, 12,13 may provide a vehicle for addressing recruitment challenges in FTD research and potentially improving sensitivity to early symptoms. We previously found that digital tests of executive functioning, which is affected across FTD syndromes, detected deficits in asymptomatic f‐FTD mutation carriers 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones, which are becoming ubiquitous, 12,13 may provide a vehicle for addressing recruitment challenges in FTD research and potentially improving sensitivity to early symptoms. We previously found that digital tests of executive functioning, which is affected across FTD syndromes, detected deficits in asymptomatic f‐FTD mutation carriers 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has suggested that remote (i.e., delivered via online or via mail) assessments are both acceptable and feasible for many participants and study partners (Geddes et al, 2020). Remote assessment has not only been shown to be feasible in young, cognitively unimpaired individuals, but also in older individuals with and without neurological and/or psychiatric disorders (D'Arcy et al, 2013;George et al, 2016;Wadsworth et al, 2016;Jacobs et al, 2021;Lavigne et al, 2021). For impaired participants, remote assessment might be preferred to reduce participant and study-partner burden as traveling into clinic becomes more physically challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Although previously reported adherence rates to online assessments vary, the rate we observed is consistent with the previous literature examining remote monitoring for more than three months. 23 , 25 , 53 , 66 Direct comparisons between adherence rates are difficult, however, due to heterogeneity in the duration of monitoring (8 days – 1 year), 25 , 53 the frequency of assessment (3 times a day – once a month), 25 , 67 and the patient population included (healthy controls or patient groups). 23 , 53 From this heterogeneity, it appears that shorter study periods demonstrate higher rates of adherence, yet our work suggests that the adherence rate over a three-month period is high enough to provide valuable insights into an individual's functional status.…”
Section: Discussionmentioning
confidence: 99%